تحسين القدرة المؤسسية لمؤسسات لتعليم الكبار في مصر: دراسة في تحليل الممكنات - قطيط، عدنان محمد أحمد (جامعة سوهاج - كلية التربية, 2022)
هدفت الدراسة الحالية إلى استكشاف الأسس النظرية والمنطلقات الفكرية لتعليم الكبار وتوجهاته الحديثة، بالإضافة إلى الوقوف على الممكنات التي يمكن من خلال توافرها تحسين أبعاد القدرة المؤسسية لهذا النمط من التعليم والتعلم وبرامجه ومؤسساته، في إطار فلسفة التعلم المستمر مدى الحياة والقائم على التوجه والدافعية الذاتية، حيث تشير الأدبيات التربوية المعاصرة إلى أنه يوجد تطور تسلسلي لنمطي البيداجوجيا والأندراجوجيا إلى ما يطلق عليه الهوتاجوجيا، ويعتبر ذلك أحد نواتج التطورات المعرفية والتقنية التي أتاحت بزوغ أنماط جديدة تراعي احتياجات المتعلم وخبراته وأهدافه. واعتمدت الدراسة في معالجتها على المنهج الوصفي، مع الاستعانة بأداة استطلاع رأي مجموعة من الخبراء وصل عددها إلى 44 خبيرًا، بهدف التعرف على وجهات نظرهم حول جدوى مجموعة من الممكنات المقترحة لتحسين القدرة المؤسسية لتعليم الكبار. وانتهت الدراسة إلى تقديم إطار من المقترحات والتوصيات الموجهة لأهم الممكنات التي تؤدي إلى تحسين القدرة المؤسسية وأبعادها المتعلقة بالحوكمة والجودة والتمويل، بما ينعكس إيجابًا على النواتج المتعلقة بالمردود والأداء العام لتعليم الكبار في مصر. The current study aimed to explore the theoretical foundations and intellectual premises of adult education and its modern trends, in addition to identifying the possibilities that can improve the dimensions of institutional capacity for this type of education and learning, its programs and institutions, within the framework of the philosophy of lifelong learning based on orientation and self-motivation. Contemporary educational literature indicates that there is a sequential development of three types of pedagogy, andragogy, and then hetagogy. The study relied on the descriptive method, with the help of a survey tool for a group of experts reached 44 experts, with the aim of identifying their views on the feasibility of a set of proposed enablers to improve the institutional capacity of adult education. The study concluded with presenting a framework of proposals and recommendations directed to the most important enablers that lead to improving institutional capacity and its dimensions related to governance, quality and financing, which will reflect positively on the outcomes related to the yield and general performance of adult education in Egypt.
Keywords: المؤسسات التعليمية -- القدرات المؤسسية -- تعليم الكبار -- التنمية المستدامة